Diabetic mastopathy - Dhanju, Avtar S.; Batra, Pranjali; Gupta, Namit; Manekar, Praneet; Khubber, Manisha; Singla, Deepshikha; Thiyagu, K.; Ohri, Poonam (International Journal of Advances in Medicine, 2021)
Diabetic mastopathy is used to describe the breast related complications of diabetes mellitus. It is a benign breast disease. Its accurate diagnosis in appropriate clinical and radiological setting shall avoid unnecessary surgical excision. Authors report a case of 25 years old female, a known case of Type 1 diabetes mellitus who presented with a rare finding of diabetic mastopathy.